The Association Between Long Working Hours of Parents and Dyslipidemia in Their Children - Ahn, Joonho; Lee, Dong-Wook; Kang, Mo-Yeol; Myong, Jun-Pyo; Chung, Mi Hae; Kim, Hyoung-Ryoul; Lee, Jongin (Frontiers in Public Health, 2022)
The purpose of our study is to examine the association between children's low-density lipoprotein cholesterol (LDL-C) levels and their parents' working hours. We used data from the 2010-2018 Korea National Health and Nutrition Examination Survey in which lipid profile samples of 3,799 children were eligible. Logistic regression analyses were used with an outcome variable of the dichotomous LDL-C group and an exposure variable of the father's and mother's working hours, respectively. In logistic regression models adjusted for age, sex, household income, education level of children and parents, and working hours of the parents, mothers’ working hours more than 52 h per week were significantly associated with their children’s dyslipidemia (OR 2.14, 95% confidence interval [CI] 1.333.47) compared to working 40 h or less, whereas fathers’ working hours did not show statistical significance (OR 1.08, 95% CI 0.711.66) in the same manner. The association was greatest for elementary school students for mothers working more than 52 h per week (OR 3.42, 95% CI 1.647.14) compared to those working hours 40 h per week or less). Mothers' long working hours were associated with a higher prevalence of dyslipidemia in their children. The association was strongest for elementary school students. Proper working time of parents is required for their children's health.